Paradygmat ekologiczny w świadomości rolników województwa kujawsko-pomorskiego - perspektywa socjologiczna - Marcysiak, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper shows the of results research on ecological awareness of chosen farmers group from kujawsko-pomorskie voivodship in the context of sustainable development. The ecological awareness is understood as the whole of ideas, values and opinions about natural environment as a place of human beings living. Within the confines of established assumptions there was taken up an exploration of issues connected to relationship between actions taken by the farmers and the natural environment. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 56-61